THE AMBIVALENCE OF REGIONAL ELECTION DISPUTE RESOLUTION IN INDONESIA: The Dynamics of the Constitutional Court's Interpretation of Dispute Resolution Designs on Regional Election Results - Humaidi, M Wildan (Program Studi Hukum Keluarga Islam, 2023)
The design of the regional elections (Pilkada, Pemilihan Kepala Daerah) court as a mechanism for resolving disputes over the results of the regional elections is experiencing changing dynamics. The dynamics of these changes are due to the different interpretations of Indonesia’s Constitutional Court (Mahkamah Konstitusi) on the regional election provisions in the 1945 Constitution. This study seeks to elaborate in depth on the inconsistencies in the Constitutional Court's interpretation of the constitutionality of regional elections, which caused ambivalence in the design of regional election dispute resolution. It employs a normative legal research model and a case approach. This research also shows the Constitutional Court's process and articulation of constitutional interpretation in constructing regional electoral justice. Based on the analysis, this study concludes that the shift in the constitutionality of regional election dispute resolution is caused by the constitutional interpretation of the phrase